An investigation into processes in English Challenge quotes in light of Functional Grammar - Nguyen Thi Quynh Hoa; Tran My Quynh (Tạp chí Khoa học và Công nghệ, 2023)
According to Halliday [1] in “An Introduction to Functional Grammar”, the process is considered as the main organized form of the clause as representation and used as a procedure to describe figures of happening, doing, sensing, saying, being or having. This article is an attempt to apply Halliday’s Functional Grammar to the identification of Processes in English Challenge Quotes (ECQs) with the aim of identifying and clarifying the nature of dominant processes demonstrated in the English Challenge Quotes, describing the verbs as part of the Processes as well as the Participants and Circumstances involved in the Processes. The data under investigation were in the form of written clauses of English Challenge Quotes collected from the website named BrainyQuote. The findings show that the Material Process is the most dominant one. It is hoped that the results of the research can illustrate the processes and provide a useful reference for people who are interested in Functional Grammar.